Placement as a Procedure for Issuing an Administrative Decision in the Judiciary of the Palestinian Supreme Court of Justice: An Analytical Study - Shubair , Mohammed Suliman Nayef (Dirasat: Shari'a and Law Sciences, 2020)
Placement is related to the administrative decision as one of the procedures required by the legislator before making some administrative decisions. This procedure is part of administrative decision-making, and is distinguished from other procedures by its mixed nature and its connection to more than one body of varying jurisdiction and degree. It is not a duty except where required by the legislator, and on this basis, the study came to shed light on the nature of placement in administrative law, the legal controls that govern it, its legal nature, the defects related to it and its impact on the administrative decision according to the judiciary of the Supreme Court of Justice. The study used an analytical approach by addressing the placement provisions by addressing the provisions and rules set by the Palestinian High Court of Justice, stating these provisions, and analyzing the relevant legal rules. The study concluded that the procedural independence between the placement and issuing authorities represents the most important control to be observed to ensure the safety of placement in particular and the administrative decision as a whole. The study recommends that the Supreme Court refrain from considering the placement defect as a formal defect of administrative decisions because placement is a preparatory procedure and not a formality of an administrative decision.